2016
DOI: 10.1111/nph.14177
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution of multiple virus‐resistance genes from a progenitor in Capsicum spp.

Abstract: SummaryPlants have evolved hundreds of nucleotide-binding and leucine-rich domain proteins (NLRs) as potential intracellular immune receptors, but the evolutionary mechanism leading to the ability to recognize specific pathogen effectors is elusive.Here, we cloned Pvr4 (a Potyvirus resistance gene in Capsicum annuum) and Tsw (a Tomato spotted wilt virus resistance gene in Capsicum chinense) via a genome-based approach using independent segregating populations.The genes both encode typical NLRs and are located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…The Sw-5b gene has been cloned and encodes a coiled-coil, nucleotide-binding, leucine-rich repeat domain (CC-NB-LRR) protein that is triggered by the TSWV cell-to-cell movement protein (NSm; Spassova et al, 2001;Hallwass et al, 2014;Peiro et al, 2014). The Tsw gene has been cloned very recently and also encodes a CC-NB-LRR protein that in this case is being triggered by the NSs RNA silencing suppressor (RSS) protein (de Ronde et al, 2013;Hedil & Kormelink, 2016;Kim et al, 2017). Although initial studies indicated that NSs proteins from natural resistance-breaking isolates of TSWV have lost avirulence and RSS activity (de Ronde et al, 2013), triggering of Tsw-based resistance in Capsicum does not require a functional RSS, as shown by a recent screen of NSs alanine substitution mutants (de Ronde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Sw-5b gene has been cloned and encodes a coiled-coil, nucleotide-binding, leucine-rich repeat domain (CC-NB-LRR) protein that is triggered by the TSWV cell-to-cell movement protein (NSm; Spassova et al, 2001;Hallwass et al, 2014;Peiro et al, 2014). The Tsw gene has been cloned very recently and also encodes a CC-NB-LRR protein that in this case is being triggered by the NSs RNA silencing suppressor (RSS) protein (de Ronde et al, 2013;Hedil & Kormelink, 2016;Kim et al, 2017). Although initial studies indicated that NSs proteins from natural resistance-breaking isolates of TSWV have lost avirulence and RSS activity (de Ronde et al, 2013), triggering of Tsw-based resistance in Capsicum does not require a functional RSS, as shown by a recent screen of NSs alanine substitution mutants (de Ronde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the presence of Pvr9 gene for poty virus resistance in the 'IHR2451' genotype. Recently Kim et al (2016) reported that Pvr4 (a poty virus resistant gene in C. annuum) and Tsw (Tomato spotted wilt virus resistant gene in C. chinense) encode for nucleotide binding and leucine rich repeat domain proteins and these multiple virus resistant genes diverged from a progenitor gene of a common ancestor in Capsicum spp. as indicated by genomic structure and coding sequences of these two genes.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are genetically linked 34 and oriented head-to-head so that they may share a promoter for simultaneous regulation of 35 transcription. Although in silico analyses revealed that NLRs with integrated domains are 36 common in higher plants, functional NLR pairs have been discovered in only a few plant 37 species (15). A more complex NLR model was reported as an 'NLR network', primarily in 38 Solanaceous plants.…”
Section: Introductionmentioning
confidence: 99%